Examining racial and social vulnerability disparities in the outpatient treatment of uncomplicated cystitis at a Southern California Academic Hospital - Caleb C. McLeod; Hadeel Al-Fayiz; Sasha Rodriguez; Karen K. Tan; Jacinda C. Abdul-Mutakabbir (Cambridge University Press, 2023)
Racially and ethnically minoritized (REM) patients are disproportionately impacted by infectious diseases. In our study, REM patients were more likely to receive care for urinary tract infections in the emergency department or urgent care, were younger, and were more likely to have higher social vulnerability.